solve for x and y
![ax + by = a - b \\ bx - ay = a + b ax + by = a - b \\ bx - ay = a + b](https://tex.z-dn.net/?f=ax+%2B+by+%3D+a+-+b+%5C%5C+bx+-+ay+%3D+a+%2B+b)
Answers
Answered by
2
hope u understand better and it will helpful to u
Attachments:
![](https://hi-static.z-dn.net/files/d9b/7cc9d627bd391b6ac77de614a8b5ea3b.jpg)
Answered by
3
Answer:
give me 5 thanks I will give you 10 thanks
Attachments:
![](https://hi-static.z-dn.net/files/d47/27941daec4d4e7632e43d4dc9b52f1e7.jpg)
Similar questions